PROSPECTS, PROBLEMS AND POSSIBLE OPPORTUNITIES OF DIGITAL CURRENCY IN BANGLADESH - Begum, Humaira (Bangladesh Journal of Multidisciplinary Scientific Research, 2021)
This study attempts to present the prospects and problems of the digital currency in Bangladesh as well around the world. To demonstrate the prospect, price and trading volume of selected ten digital currencies being presented for observing the emerging the demand. From our country’s perspective, the opinions of the respondents collected through questionnaires shed light on the prospect of digital currency in Bangladesh. Additionally, the study presents a systematic literature review (SLR) of research on digital currency. The review incorporated 11 articles presenting several issues related to digital currency. This study uses data from 2013 to 2020 for respective currencies related to price and trading volume. As well respondent’s opinions collected through “questionnaires” are presented as per percentage. This study also makes theoretical contributions to the extant literature. The findings demonstrate that digital currency is now successfully traded in the most countries around the world except a few. Descriptive statistics of price and trading volume indicate that most of the variables are highly skewed with large outliers and kurtosis column shows that all the variables are near to normal distribution and investment regarding these values indicates a safe trading. The consents of 175 respondents present a positive attitude of the general public towards digital currency. The SLR methods suggest that a secure system and advanced technology should be attached to the block chain system to ensure better performance. The SLR findings also point out that digital currency is obviously a better alternative to cash, although it has some risks.